Answers

2015-01-21T20:58:43+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
BY SUBSTITUTION :
equation 1 : x-3y=1 ; x=1+3y
equation 2 : 2x+3y=-4

1 -> 2 : 2(1+3y)+3y=-4
2+6y+3y=-4
9y=-6
y=-2/3

x=1+3(-2/3) = 1-2 = -1
(-1,-2/3)

BY ELIMINATION :

multiply the first equation by 2 which results to 2x-6y=2 then subtract it to equation 2 to get 0x-9y=6 solve for y; y=-2/3 then substitute y to equation 1 to get x=-1
0
Thank you po! =D
idk how to make matrix for you here sorry
No It's okay :) :D